2019
DOI: 10.3389/fpls.2019.00215
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar Differences and Impact of Plant-Plant Competition on Temporal Patterns of Nitrogen and Biomass Accumulation

Abstract: Current niche models cannot explain multi-species plant coexistence in complex ecosystems. One overlooked explanatory factor is within-growing season temporal dynamism of resource capture by plants. However, the timing and rate of resource capture are themselves likely to be mediated by plant-plant competition. This study used Barley ( Hordeum sp.) as a model species to examine the impacts of intra-specific competition, specifically inter- and intra-cultivar competition on the temporal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Leucine aminopeptidase root associated area also demonstrated a delay in activity but only when Proctor was in intra-cultivar competition. This delay in leucine aminopeptidase root associated area when in intra-cultivar competition echoes a similar trend to the delay of 14.5 days in Proctor peak above-ground nitrogen accumulation rate found in a previous study (Schofield et al, 2019). The mechanism that links these two observations is not clear.…”
Section: -Root Associated Areasupporting
confidence: 81%
See 3 more Smart Citations
“…Leucine aminopeptidase root associated area also demonstrated a delay in activity but only when Proctor was in intra-cultivar competition. This delay in leucine aminopeptidase root associated area when in intra-cultivar competition echoes a similar trend to the delay of 14.5 days in Proctor peak above-ground nitrogen accumulation rate found in a previous study (Schofield et al, 2019). The mechanism that links these two observations is not clear.…”
Section: -Root Associated Areasupporting
confidence: 81%
“…where sampling occurred in the first month of growth, the period prior to peak nitrogen accumulation rate in these barley cultivars (Schofield et al, 2019). This is likely to be a period of soil microbial community priming to mine for nitrogen within soil organic matter and may account for the differences between Ma et al's and our study.…”
Section: -Temporal Dynamics Of Enzyme Activity In Response To Plant-pmentioning
confidence: 64%
See 2 more Smart Citations
“…The study of Trinder et al (2012) was conducted with perennial grassland species, and annual crop species might react differently to neighbor presence. For example, a study using two barley cultivars – one early and one late - grown as isolated single plants and in either intra- or inter-specific competition (Schofield et al 2019b) found peak N accumulation was advanced by 0.5 days for the early and delayed by 14.5 days for the late cultivar when in intra-specific competition, while no shifts were observed in inter-specific competition. This suggests crop species may have enough temporal plasticity to avoid competition with kin but not with other species.…”
Section: Discussionmentioning
confidence: 99%